The Effect of The 5s Culture (Smile, Greeting, Hellogreeting, Polite And Courtesy) on The Social Ethics of Elementary School Students - Hendrawan, Mohammad Gilang; Agustin, Mubiar; Asyiah, Lutfi Fitri (International Conference on Elementary Education, 2025)
The low level of social ethics among elementary school students, reflected in rude behavior and a lack of respect for teachers and peers, underscores the urgency of instilling social values through a positive school culture. This study aimed to analyze the influence of the 5S Culture (Smile, Greet, Say Hello, Be Polite, and Be Courteous) on the social ethics of elementary school students. The research used a qualitative descriptive method involving 28 fourth-grade students from one public elementary school in Bandung City, Indonesia, where the 5S Culture had been systematically implemented for more than six months. Data were collected through questionnaires, field observations, and documentation, and analyzed through data reduction, coding, and interpretation. The findings revealed that approximately 60% of students demonstrated noticeable improvement in social ethics indicators such as politeness, honesty, cooperation, and empathy after the consistent implementation of the 5S Culture. Students became more respectful and responsible in their interactions, particularly toward teachers and senior peers. These results confirm that the 5S Culture effectively strengthens students’ social behavior and supports Sustainable Development Goal 4 (Quality Education) by fostering inclusive, respectful, and value-based learning environments.